2021
DOI: 10.1038/s41598-021-99689-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of COVID-19 lockdown on river water quality: evidence from River Damodar, India

Abstract: The global economic activities were completely stopped during COVID-19 lockdown and continuous lockdown partially brought some positive effects for the health of the total environment. The multiple industries, cities, towns and rural people are completely depending on large tropical river Damodar (India) but in the last few decades the quality of the river water is being significantly deteriorated. The present study attempts to investigate the river water quality (RWQ) particularly for pre- lockdown, lockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In terms of environmental pollution, greenhouse gas emissions, nitrogen dioxide, black carbon, and water contamination have decreased significantly ( Chakraborty and Maity, 2020 ). In India, several studies conducted on different rivers have found a reduction in industrial waste contamination and an improvement in water quality of about 40–50%, also leading to a reduction in heavy metal concentrations ( Chakraborty B. et al, 2021 ; Chakraborty, S. et al, 2021 ; Shukla et al, 2021 ). Therefore, continuous monitoring of ecosystems is necessary and valuable to obtain real-time information on environmental quality.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environmental pollution, greenhouse gas emissions, nitrogen dioxide, black carbon, and water contamination have decreased significantly ( Chakraborty and Maity, 2020 ). In India, several studies conducted on different rivers have found a reduction in industrial waste contamination and an improvement in water quality of about 40–50%, also leading to a reduction in heavy metal concentrations ( Chakraborty B. et al, 2021 ; Chakraborty, S. et al, 2021 ; Shukla et al, 2021 ). Therefore, continuous monitoring of ecosystems is necessary and valuable to obtain real-time information on environmental quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, not only the air quality was improved due to the COVID-19 first phase lockdown, but also the surface water quality was considerably enhanced and water pollution of ecological environment has been reduced through the natural purification process ( Chakraborty et al, 2021c ). During the several phases of lockdown ( Dutta et al, 2020 ), pollutant loads such as industrial effluents, urban sewages, agricultural sewages, wastewater etc.…”
Section: Introductionmentioning
confidence: 99%
“…The improvements in water quality were witnessed also in terms of decreases in biological oxygen demand (BOD W ). Chakraborty et al ( 2021b ) reported about 28% decrease in BOD during lockdown period in the Damodar River. Pant et al ( 2021 ) observed about 1.5 and 1.9 time decrease in BOD and COD respectively during lockdown in Bagmati River (Nepal).…”
Section: Discussionmentioning
confidence: 99%
“…At the most polluted industrial site (Wpdr), the concentrations of NO 3 − , NH 4 + , PO 4 − , and TOC declined by 18%, 14%, 17%, and 19% respectively in the 2020 compared to the 2019. For the Damodar River, the concentrations of total phosphorus and nitrate declined by about 70% and 57% respectively during lockdown compared to no-lockdown period (Chakraborty et al 2021b ). In a human-impacted coastal area of Malaysia, Kamarudin et al ( 2021 ) reported about 11.5% decline in nitrate and about 77.2% decline in phosphate under the influence of COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%